ASSESSMENT OF THE IMMUNE CELL LANDSCAPE IN INFLAMMATORY BOWEL DISEASE. (26th January 2023) - Martinez, Evelyn Calderon; Zevallos-Delgado, Christian; Ng, Wern Lynn; Gautam, Seema Sharma; Joseph, Maria
Abstract: INTRODUCTION: Inflammatory Bowel Disease (IDB) is a chronic and sometimes refractory group of gastrointestinal conditions that can cause enormous medical and socioeconomic burdens. [1] Both, innate and adaptive immune cells play a crucial role in the pathogenesis of IBD, but the exact mechanisms are not totally well understood [2] An improved understanding of the immune cell landscape behind IBD is necessary for identifying novel diagnostic and therapeutic targets. OBJECTIVE: The aim of this study was to evaluate and compare the immune cell composition between healthy patients and patients with Ulcerative Colitis (UC) and Chron's Disease (CD) in peripheral blood and colon biopsy samples. METHODOLOGY: The immune cell landscape in peripheral blood and colon biopsy samples was determined using CIBERSORT and gene expression data from the study submitted by Argmann et al obtained via Gene Expression Omnibus (peripheral blood: GSE186507 and colon biopsies: GSE193677). In this study the biopsies were obtained from ileum, colon, and rectum. T-test was used to estimate the differences among the groups. RESULTS: The immune cell landscape of peripheral blood showed more resting T CD4 memory cells in the control group (p=0.009), while the number of activated T CD4 memory cells was greater in IBD patients (p= 0.01). The frequency of B cells naïve was higher in CD than in UC (p= 0.03), and CD8 T cells were more in UC (p=0.04). In terms of biopsies, the samples from the rectum showed the highest infiltration of immune cells. Macrophages M1 are present with higher numbers in rectum samples from CD vs UC (p=0.0026) and CD vs control group (p=8e-10). CONCLUSIONS: The results showed significant differences in the immune cell composition among the control group, UC, and CD patients, not only in peripheral blood but also in biopsy samples. In both cases, Macrophages M1 were the most common cells found. These findings suggest that immune cell landscape could be used as a potential biomarker of the progression of IBD.